Sushi Diplomacy as an Instrument of Gastrodiplomacy Implications for Japan’s Public Diplomacy and National Identity - Roy Setiawan; Muhammad Aditya Purnomo; Arina Nihayati (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
This study examines the strategic use of sushi as a central instrument in Japan’s gastrodiplomacy, aiming to enhance public diplomacy, soft power, and national identity on the global stage. Utilizing a qualitative case study design combined with media discourse analysis, the research maps the engagement of state and non-state actors—including government agencies, renowned chefs, international restaurants, and digital media platforms—in shaping cultural narratives through culinary diplomacy. Data are drawn from policy documents, academic literature, global media sources, and digital trend analysis via Brand24. The findings reveal that sushi serves not only as a gastronomic product but also as a cultural symbol representing Japanese values, including aesthetics, omotenashi (hospitality), health consciousness, and craftsmanship. Cross-sector collaborations have fostered a dynamic diplomatic ecosystem that advances Japan’s cultural positioning while stimulating trade and tourism. Challenges persist in managing authenticity and commercialization, particularly in markets where sushi has undergone significant local adaptation. Compared to gastrodiplomacy campaigns such as Thai Select and Kimchi Diplomacy, Japan’s approach is marked by strategic flexibility and a commitment to preserving culinary heritage. This study enriches scholarly discourse by providing a comprehensive conceptual mapping of sushi diplomacy as a geopolitical tool and cultural branding strategy, offering practical insights for policymakers and cultural practitioners seeking to leverage cuisine in international engagement. Keywords: sushi diplomacy, gastrodiplomacy, soft power, public diplomacy, cultural identity